Reciprocal Regulation of V-ATPase and Glycolytic Pathway Elements in Health and Disease - Hayek, Summer R.; Rane, Hallie S.; Parra, Karlett J. (Frontiers in Physiology, 2019)
The ability of cells to adapt to fluctuations in glucose availability is crucial for their survival and involves the vacuolar proton-translocating ATPase (V-ATPase), a proton pump found in all eukaryotes. V-ATPase hydrolyzes ATP via its V1 domain and uses the energy released to transport protons across membranes via its Vo domain. This activity is critical for pH homeostasis and generation of a membrane potential that drives cellular metabolism. A number of stimuli have been reported to alter V-ATPase assembly in yeast and higher eukaryotes. Glucose flux is one of the strongest and best-characterized regulators of V-ATPase; this review highlights current models explaining how glycolysis and V-ATPase are coordinated in both the Saccharomyces cerevisiae model fungus and in mammalian systems. Glucose-dependent assembly and trafficking of V-ATPase, V-ATPase-dependent modulations in glycolysis, and the recent discovery that glucose signaling through V-ATPase acts as a molecular switch to dictate anabolic versus catabolic metabolism are discussed. Notably, metabolic plasticity and altered glycolytic flux are critical drivers of numerous human pathologies, and the expression and activity of V-ATPase is often altered in disease states or can be pharmacologically manipulated as treatment. This overview will specifically discuss connections between V-ATPase and glycolysis in cancer.